(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the outcomes such as recurrence, complications, hospital stay and pain of antibiotic therapy and appendectomy in patients presented with acute appendicitis. Study Design: Comparative study. Place and Duration of Study: The study was conduct Department of Surgery, Bolan University of Medical & Health Sciences, Quetta from July 2017 to August 2019. Materials and Methods: Eighty patients of both genders presented with acute appendicitis were included. Patient’s demographical details were recorded after written consent. Patients were equally divided into two groups i.e. Group I consist of 40 patients and received appendectomy, Group II consist of 40 patients and received antibiotics. Outcomes such as recurrence, pain, hospital stay and complications were examined and compare the findings between both groups. SPSS 21.0 was used to analyze the data. Results: Fifty three (66.25%) were male (Group I 28, Group II 25) with mean age 32.2±7.6 years and 27 (33.75%) were females (12 Group I, 15 Group II) with mean age of 31.5±9.1 years. Group I patients had less hospital stay, recurrence rate and pain score as compared to Group II patients (p-value <0.05). In Group I patients wound infection was the most common complication found in 10 (25%) patients and in Group II appendicular mass was most common complication found in 12 (30%) patients. Conclusion: Appendectomy is very effective and better treatment modality as compared to antibiotic therapy for acute appendicitis.